Brn3a and Nurr1 Mediate a Gene Regulatory Pathway for Habenula Development - Quina, Lely A. (Society for Neuroscience, 2009)
The habenula is a dorsal diencephalic structure consisting of medial and lateral subnuclei and a principal output tract, the fasciculus retroflexus, which together form a link between the limbic forebrain and ventral midbrain. Here, we have used microarray and bioinformatic approaches in the mouse to show that the habenula is a distinctive molecular territory of the CNS, with a unique profile of neurotransmitter, ion channel, and regulatory factor expression. Neurons of the medial habenula and part of the lateral habenula express the transcription factor Brn3a/Pou4f1, and Brn3a-expressing habenular neurons project exclusively to the interpeduncular nucleus in the ventral midbrain. In Brn3a mutant embryos, the fasciculus retroflexus is directed appropriately, but habenular neurons fail to innervate their targets. Microarray analysis of Brn3a null embryos shows that this factor regulates an extensive program of habenula-enriched genes, but not generic neural properties. The orphan nuclear receptor Nurr1/Nr4a2 is coexpressed with Brn3a in the developing habenula, is downstream of Brn3a, and mediates expression of a subset of Brn3a-regulated transcripts. Together, these findings begin to define a gene regulatory pathway for habenula development in mammals.